Priceless, ground-based data for solar flare observers.
We know that the chromosphere is where most solar flare radiations originate from, but gaps do remain in our understanding of their relevant physics. A consortium led by the University of Glasgow recently made an important contribution in this regard : using both space-based and ground-based data, it defines where future efforts should be targeted, and identifies where long-standing ideas about how energy travels through the solar atmosphere in a flare are in agreement-or disagreement-with observations.